2018
DOI: 10.1102/2051-7726.2018.0001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 3D laparoscopic surgical training on performance in standard 2D laparoscopic simulation: a randomised prospective study

Abstract: Background: Laparoscopic surgery is based on 2D imaging, with limited depth perception. The aim of this study was to analyse the impact of 3D training on the performance of surgical trainees in 2D laparoscopic simulation. Methods: Thirty medical students were randomised into group A, completing five training attempts of three modified Fundamentals of Laparoscopic Surgery tasks (peg transfer, pattern cutting, and intra-corporeal suturing) using a 3D simulator, or group B, who were only exposed to the 2D platfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In recent years, some high-quality randomized controlled trials have shown that, compared with 2D laparoscopy, the application of 3D laparoscopy in basic operation training may shorten the duration of operation, reduce operation errors, and improve operation accuracy ( 16 19 ). Some researchers have studied the use of 2D and 3D laparoscopic techniques, such as grasping, cutting, suturing, and knotting, to simulate the basic operations of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some high-quality randomized controlled trials have shown that, compared with 2D laparoscopy, the application of 3D laparoscopy in basic operation training may shorten the duration of operation, reduce operation errors, and improve operation accuracy ( 16 19 ). Some researchers have studied the use of 2D and 3D laparoscopic techniques, such as grasping, cutting, suturing, and knotting, to simulate the basic operations of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with 2D laparoscopy, 3D laparoscopy can restore the real 3D anatomical structure, which is mainly reflected in the shortened operation time, the reduction of operation errors and the improvement of operation accuracy. [ 18 ] Therefore, 3D laparoscopy was used in this study. In the process of conducting complex and delicate operations and the separation of important anatomical layers, the 3D images and magnified views generated a clear surgical field more clear and a strong sense of depth.…”
Section: Discussionmentioning
confidence: 99%
“…11 These findings are similar to the findings of Almeida et al who concluded that 3D laparoscopic techniques are beneficial for naive surgeons to better understand the relations of various structures. 12 Bilgen et al have reported that 3D laparoscopic cholecystectomies are superior than 2D laparoscopic cholecystectomies. 13 …”
Section: Discussionmentioning
confidence: 99%